Sealant film, external material for secondary battery, secondary battery, and motor device
A multi-layer sealant film with high-melting-point polypropylene and cyclic olefin resins addresses the challenges of sealing and water vapor barrier properties at high temperatures, providing enhanced performance for secondary and all-solid-state batteries.
Patent Information
- Application Number
- JP2023093684
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional sealant films for lithium secondary batteries and all-solid-state batteries face challenges in maintaining sealing properties, water vapor barrier properties, and moldability at high temperatures, with issues such as void formation and insufficient compatibility with high-temperature sealing performance.
A sealant film composed of multiple layers, including a high-melting-point polypropylene resin layer and cyclic olefin resin layers, with specific resin content and structural configurations to enhance sealing strength, water vapor barrier properties, and moldability, featuring a co-continuous structure and controlled resin composition.
The sealant film achieves excellent sealing strength, water vapor barrier properties, and moldability at high temperatures, suitable for use in secondary batteries and all-solid-state batteries, particularly enhancing the performance of exterior materials.
Smart Images

Figure 2024175735000002 
Figure 2024175735000003 
Figure 2024175735000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealant film that is excellent in sealing properties at high temperatures, water vapor barrier properties, and formability. [Background technology]
[0002] Lithium secondary batteries have a higher energy density than other secondary batteries and are used as batteries for electric vehicles and power storage.
[0003] Conventionally used lithium secondary batteries using non-aqueous electrolytes use a lithium hexafluorophosphate solution as the electrolyte, but from a safety standpoint, they need to be used at temperatures below 60° C. In addition, the electrolyte reacts with moisture to generate hydrofluoric acid, which permeates the inner layer of the laminate and reduces the adhesion between the metal foil and the inner layer, causing peeling and shortening the battery life, so various studies have been conducted to suppress the penetration of moisture (Patent Documents 1 to 3).
[0004] Moreover, all-solid-state lithium secondary batteries (hereafter referred to as all-solid-state batteries), which have been attracting attention in recent years, use solid electrolytes instead of the electrolyte solutions that have been widely used in conventional non-aqueous electrolytes. Since all-solid-state batteries do not use organic solvents in the battery, they have the advantages of being highly safe and having a wide operating temperature range, and because they are easy to achieve high efficiency at temperatures above 60°C, the sealant films used as the exterior materials for all-solid-state batteries must also be designed with the possibility of being used at high temperatures above 60°C in mind.
[0005] In addition, when a sulfide solid electrolyte is used in an all-solid-state battery, if moisture enters the battery, the solid electrolyte reacts with the moisture to generate sulfur-based gas, which is a problem. Specifically, there is concern that if the battery is used for a long period of time, the sulfur-based gas will accumulate, causing the battery exterior material to expand or break.
[0006] At high temperatures, the water vapor barrier properties of the sealant film constituting the exterior material decrease, and therefore the methods for improving the water vapor barrier properties that have been proposed up to now may not be sufficiently effective. As a further method for improving the water vapor barrier properties, a method has been proposed in which an inorganic absorbent is used in the sealant film (Patent Document 4).
[0007] Furthermore, Patent Document 5 proposes a method of using a resin with a high melting point or glass transition point in a sealant film as a method for improving the sealability at high temperatures. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2015-38881 A [Patent Document 2] JP 2008-293909 A [Patent Document 3] JP 2007-26682 A [Patent Document 4] Patent Publication No. 2021-57231 [Patent Document 5] JP 2021-108263 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, when an inorganic absorbent as described in Patent Document 4 is used in a sealant, there is a concern that defects such as voids may occur in the sealant film when it is molded into a pouch. In addition, there is a concern that the sealant film described in Patent Document 5 may not be able to sufficiently balance sealing properties and moldability at high temperatures.
[0010] An object of the present invention is to provide a sealant film for exterior packaging which has excellent sealing properties at high temperatures, water vapor barrier properties and formability. [Means for solving the problem]
[0011] Preferred aspects of the present invention are as follows. (1) A sealant film having at least a layer A, a layer B, and a layer C directly in that order, in which the layer A has a melting point of 135°C or higher and contains a polypropylene-based resin, and at least the layers B and C contain a cyclic olefin-based resin, with the content of the cyclic olefin-based resin in each layer being greatest in the order of the layer C, the layer B, and the layer A. (2) A sealant film having at least a layer A, a layer B, and a layer C directly in this order, in which layer B has a cocontinuous structure consisting of a cyclic olefin resin and other resins, and layer A contains a total of 60 mass% or more of resins selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of layer A is 100 mass%, and layer C contains a total of 60 mass% or more of resins selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of layer C is 100 mass%. (3) A sealant film according to (1) or (2), in which the layer B contains 30% by mass or more and 70% by mass or less of a cyclic olefin resin relative to 100% by mass of the total mass of the layer B. (4) The sealant film according to (3), wherein layer B contains a compatibilizer for the cyclic olefin resin and the polypropylene resin. (5) A sealant film according to (1) or (2), in which the C layer contains 60% by mass or more of a cyclic olefin resin relative to 100% by mass of the total mass of the C layer. (6) A sealant film according to (1) or (2), which has five layers laminated directly in the order of layer A, layer B, layer C, layer B, and layer A. (7) A sealant film according to (1) or (2), in which at least one of the surfaces has a static friction coefficient of 0.5 or less and a ten-point average roughness of the surface of 2.0 μm or more. (8) Water vapor permeability at 60°C and 90% RH is 3 g mm / m 2 / day or less. (9) A sealant film according to (1) or (2), in which the peel strength in an atmosphere at 100°C after the A layers are heat-sealed to each other is 10 N / 15 mm or more. (10) A sealant film according to (1) or (2), which is used for a molded article having a drawing depth of 5 mm or more. (11) The sealant film for exterior materials according to (1) or (2), which is used as an exterior material for an all-solid-state battery. (12) An exterior material for a secondary battery, comprising the sealant film according to (1) or (2). (13) A secondary battery comprising the exterior packaging material according to (12). (14) An electric device having the secondary battery according to (13). Effect of the Invention
[0012] According to the present invention, it is possible to provide a sealant film that is excellent in sealing strength at high temperatures, water vapor barrier properties, and formability. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic diagram of an example of a layer having a sea-island structure when observed in cross section. [Diagram 2] FIG. 2 is a schematic diagram of an example of a layer having a co-continuous structure when observed in cross section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Preferred aspects of the embodiment of the present invention will now be described.
[0015] One preferred embodiment of the present invention is a sealant film having at least a layer A, a layer B, and a layer C directly in that order, in which layer A has a melting point of 135°C or higher and contains a polypropylene-based resin, and at least layers B and C contain a cyclic olefin-based resin, with the content of cyclic olefin-based resin in each layer being greatest in the order of layer C, layer B, and layer A.
[0016] A second preferred embodiment of the present invention is a sealant film having at least a layer A, a layer B, and a layer C directly in this order, in which layer B has a cocontinuous structure consisting of a cyclic olefin resin and other resins, and layer A contains a total of 60 mass% or more of resins selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of layer A is taken as 100 mass%, and layer C contains a total of 60 mass% or more of resins selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of layer C is taken as 100 mass%.
[0017] The A layer constituting the sealant film of the present invention preferably has a melting point of 135° C. or higher from the viewpoint of improving the seal strength at high temperatures. The A layer preferably has a melting point of 140° C. or higher, more preferably 145° C. or higher, from the viewpoint of improving the seal strength at high temperatures, and preferably has a melting point of 170° C. or lower from the viewpoint of improving the moldability and low-temperature sealability. The method for measuring the melting point will be described later, and when there are two or more melting points, it is preferable that the higher melting point is 135° C. or higher.
[0018] In addition, the A layer constituting the sealant film of the present invention preferably contains a polypropylene-based resin from the viewpoint of achieving both high-temperature seal strength, moldability, and water vapor barrier properties. The content of the polypropylene-based resin in the A layer is preferably 50% by mass or more, and more preferably 60% by mass or more, when the entire A layer is taken as 100% by mass, from the viewpoint of improving the seal strength and moldability at high temperatures. The upper limit of the content of the polypropylene-based resin in the A layer is more preferably 90% by mass or less, and even more preferably 80% by mass or less, from the viewpoint of improving the adhesion with the B layer.
[0019] The polypropylene-based resin used in layer A of the sealant film of the present invention is preferably one or more polypropylene-based resins selected from homopolypropylene, random copolymers of propylene and ethylene and / or butene-1, and block copolymers containing homopolypropylene and ethylene-propylene copolymer.
[0020] The melting point of the polypropylene resin used in layer A is preferably 135° C. or higher, more preferably 140° C. or higher, and even more preferably 145° C. or higher, from the viewpoint of controlling the melting point of layer A to 135° C. or higher and improving the seal strength at high temperatures and the water vapor barrier property at high temperatures. The upper limit of the melting point of the polypropylene resin is substantially 170° C. or lower.
[0021] The melt flow rate (MFR) of the polypropylene resin measured at 230°C under a load of 21.18 N is preferably 1.0 g / 10 min or more, more preferably 2.0 g / 10 min or more, from the viewpoints of film-forming property, dispersibility with the cyclic polyolefin resin in layer A and other resins, and sealability when heat-sealing layers A together. The upper limit of the MFR of the polypropylene resin is preferably 15 g / 10 min or less, more preferably 10 g / 10 min or less, from the viewpoints of favorably controlling the seal strength, moldability, film-forming property, and dispersibility with the cyclic polyolefin resin and other resins.
[0022] In addition to the polypropylene resin, the layer A of the present invention may contain a cyclic olefin resin, a thermoplastic resin other than these, and an additive, as long as the object of the present invention is not impaired. When the layer A of the present invention contains a cyclic olefin resin, the content is preferably 5% by mass or more from the viewpoint of improving adhesion with the layer B and improving water vapor barrier properties, and is preferably 30% by mass or less from the viewpoint of improving the seal strength when the layers A are heat sealed together. When a thermoplastic resin other than a polypropylene resin and a cyclic olefin resin is contained in the layer A, the amount added may be appropriately adjusted according to the desired physical properties, but from the viewpoint of the balance of seal strength at high temperatures, water vapor barrier properties, and moldability, the content is preferably 2% by mass or more and preferably 30% by mass or less.
[0023] The cyclic olefin resin mentioned above is a resin obtained by polymerization of a cyclic olefin monomer, and has an alicyclic structure in the main chain of the polymer, and means a polymer in which the total amount of components (structural units) derived from the cyclic olefin monomer is more than 50 mass% and not more than 100 mass% in 100 mass% of the polymer of the cyclic olefin resin.
[0024] Cyclic olefin monomers include monocyclic olefins such as cyclobutene, cyclopentene, cycloheptene, cyclooctene, cyclopentadiene, and 1,3-cyclohexadiene; bicyclo[2.2.1]hept-2-ene, 5-methyl-bicyclo[2.2.1]hept-2-ene, 5,5-dimethyl-bicyclo[2.2.1]hept-2-ene, 5-ethyl-bicyclo[2.2.1]hept-2-ene, 5-butyl-bicyclo[2.2.1]hept-2-ene, 5-ethylidene-bicyclo[2.2.1]hept-2-ene, 5-hexyl-bicyclo[2.2.1]hept-2-ene, 5-octyl-bicyclo[2.2.1]hept-2-ene, 5-octadecyl-bicyclo[2.2.1]hept-2-ene, and 5-methylidene- Bicyclic olefins such as bicyclo[2.2.1]hept-2-ene, 5-vinyl-bicyclo[2.2.1]hept-2-ene, and 5-propenyl-bicyclo[2.2.1]hept-2-ene; tricyclo[4.3.0.1 2,5 ]Deca-3,7-diene, tricyclo〔4.3.0.1 2,5 ]deca-3-ene, tricyclo〔4.3.0.1 2,5 ]Undeca-3,7-diene, Tricyclo〔4.3.0.1 2,5 ]Undeca-3,8-diene, Tricyclo〔4.3.0.1 2,5 ]undec-3-ene, 5-cyclopentyl-bicyclo[2.2.1]hept-2-ene, 5-cyclohexyl-bicyclo[2.2.1]hept-2-ene, 5-cyclohexenyl-bicyclo[2.2.1]hept-2-ene, 5-phenyl-bicyclo[2.2.1]hept-2-ene, tricyclic olefins such as tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyltetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-ethyltetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methylidenetetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-ethylidenetetracyclo〔4.4.0.1 2,5 .17,10 ]dodec-3-ene, 8-vinyltetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-propenyl-tetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, and tetracyclic olefins such as 8-cyclopentyl-tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-cyclohexyl-tetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-cyclohexenyl-tetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-phenyl-cyclopentyl-tetracyclo〔4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, tetracyclo〔7.4.1 3,6 .0 1,9 .0 2,7 ]Tetradeca-4.9.11.13-tetraene, tetracyclo[8.4.1 4,7 .0 1,10 .0 3,8 ]Pentadeca-5.10.12.14-tetraene, Pentacyclo[6.6.1 3,6 .0 2,7 .0 9,14 ]-4-Hexadecene, Pentacyclo〔6.5.1.1 3,6 .0 2,7 .0 9,13 ]-4-pentadecene, pentacyclo〔7.4.0.0 2,7 .1 3,6 .1 10,13 ]-4-pentadecene, heptacyclo〔8.7.0.1 2,9 .1 4,7 .1 11,17 .0 3,8 .0 12,16 ]-5-Eicosene, heptacyclo〔8.7.0.1 2,9 .0 3,8 .1 4,7 .0 12,17 .11 3,16]-14-eicosene, cyclopentadiene, and other polycyclic olefins such as tetramers. These cyclic olefin monomers can be used alone or in combination of two or more.
[0025] Among the above-mentioned cyclic olefin monomers, from the viewpoint of productivity and the like, bicyclo[2.2.1]hept-2-ene (hereinafter referred to as norbornene), tricyclo[4.3.0.1 2,5 ]dec-3-ene and other tricyclic olefins having 10 carbon atoms (hereinafter referred to as tricyclodecene), tetracyclo[4.4.0.1 2,5 .1 7,10 ] A tetracyclic olefin having 12 carbon atoms such as dodec-3-ene (hereinafter referred to as tetracyclododecene), cyclopentadiene, or 1,3-cyclohexadiene is preferably used.
[0026] The cyclic olefin resin may be either a resin obtained by polymerizing only the above-mentioned cyclic olefin monomer (hereinafter sometimes referred to as COP) or a resin obtained by copolymerizing the above-mentioned cyclic olefin monomer with a chain olefin monomer (hereinafter sometimes referred to as COC), so long as the total content of components derived from the cyclic olefin monomer in 100% by mass of the cyclic olefin resin polymer is more than 50% by mass and not more than 100% by mass.
[0027] Examples of the method for producing COP include known methods such as addition polymerization or ring-opening polymerization of cyclic olefin monomers, such as a method of subjecting norbornene, tricyclodecene, tetracyclodecene, and derivatives thereof to ring-opening metathesis polymerization followed by hydrogenation, a method of addition polymerization of norbornene and derivatives thereof, a method of subjecting cyclopentadiene and cyclohexadiene to 1,2-, 1,4-addition polymerization followed by hydrogenation, etc. Among these, from the viewpoints of productivity and moldability, a resin obtained by subjecting norbornene, tricyclodecene, tetracyclodecene, and derivatives thereof to ring-opening metathesis polymerization followed by hydrogenation is most preferred.
[0028] In the case of COC, preferred linear olefin monomers include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Among these, ethylene is particularly preferably used from the viewpoint of productivity and cost. In addition, as a method for producing a resin obtained by copolymerizing a cyclic olefin monomer and a linear olefin monomer, known methods such as addition polymerization of a cyclic olefin monomer and a linear olefin monomer can be mentioned, for example, a method of addition polymerization of norbornene and its derivatives with ethylene. Among these, a copolymer of norbornene and ethylene is most preferred from the viewpoints of productivity and moldability.
[0029] In the sealant film of the present invention, the above-mentioned cyclic olefin resins may be used alone or in combination of two or more.
[0030] The glass transition point of the cyclic olefin resin is preferably 60° C. or higher, more preferably 80° C. or higher, and even more preferably 100° C. or higher, from the viewpoint of improving the water vapor barrier property. The upper limit of the glass transition point of the cyclic olefin resin of the present invention is preferably 200° C., more preferably 150° C., and even more preferably 130° C., from the viewpoint of improving the moldability.
[0031] As a method for controlling the glass transition point of the cyclic olefin resin of the present invention, for example, when a copolymer of norbornene and ethylene is used as the COC, the glass transition point can be increased by increasing the content of norbornene in the COC. Furthermore, the glass transition point can be adjusted by blending two types of COC that have different norbornene contents and are compatible with each other. Furthermore, when a resin obtained by subjecting norbornene, tricyclodecene, tetracyclododecene, and derivatives thereof to ring-opening metathesis polymerization and then hydrogenating the resin is used as the COP, the glass transition point can be increased by increasing the molecular weight of the cyclic olefin to be polymerized (norbornene, tricyclodecene, tetracyclododecene, and derivatives thereof) or increasing the number of rings to give a rigid structure. Furthermore, the glass transition point of the cyclic olefin resin of the present invention can be adjusted by blending two types of COP that have different glass transition points and are compatible with each other.
[0032] Cyclic olefin resin at 230℃ and shear rate of 121s -1 The melt viscosity measured by is preferably 300 Pa s or more from the viewpoint of film formability when the sealant film is melt extruded and dispersibility when it is blended with polypropylene resins or other thermoplastic resins, and from the same viewpoint, is preferably 2000 Pa s or less, and more preferably 1000 Pa s or less.
[0033] When a thermoplastic resin other than a polypropylene resin and a cyclic olefin resin is added to layer A, it is preferable to use one or more thermoplastic resins selected from polyethylene resins such as high density polyethylene (HDPE), low density polyethylene (LDPE), and linear low density polyethylene (LLDPE), ethylene-α-olefin copolymers, propylene-α-olefin copolymers, ethylene copolymers, 4-methyl-1-pentene copolymers, ethylene propylene diene rubber, olefin thermoplastic elastomers, copolymers of ethylene and vinyl carboxylate such as ethylene-vinyl acetate copolymer (EVA), ethylene-vinyl propionate copolymer, and ethylene-vinyl butanoate copolymer, copolymers of ethylene and α,β-unsaturated carboxylic acid alkyl ester such as ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-butyl acrylate copolymer (EBA), and ethylene-methyl methacrylate copolymer (EMMA), polybutylene terephthalate films, and resins obtained by copolymerizing these with maleic anhydride.
[0034] The melt flow rate (MFR) of thermoplastic resins other than polypropylene resins and cyclic olefin resins measured at 230°C under a load of 21.18 N is preferably 1.0 g / 10 min or more, more preferably 2.0 g / 10 min or more, from the viewpoints of film-forming property, dispersibility with polypropylene resins in layer A, and sealability when heat-sealing layers A together. The upper limit of the MFR of the thermoplastic resin is preferably 30 g / 10 min or less, from the viewpoints of seal strength, moldability, film-forming property, and dispersibility with polypropylene resins.
[0035] The B layer and C layer of the sealant film of the present invention preferably contain a cyclic olefin-based film, and the same resin as the above-mentioned cyclic olefin-based resin can be preferably used. In addition, from the viewpoint of favorably controlling the balance between the sealability at high temperatures, the water vapor barrier property, and the moldability of the sealant film of the present invention, the content of the cyclic olefin-based resin used in each layer of the sealant film is preferably greater in the order of C layer, B layer, and A layer. In other words, the content of the cyclic olefin-based resin used in each layer of the sealant film is the greatest in C layer, and the least in A layer.
[0036] When the total mass of each layer is 100% by mass, the content of the cyclic olefin resin in Layer C is preferably 5% by mass or more, and more preferably 10% by mass or more, higher than the content of the cyclic olefin resin in Layer B. Also, the content of the cyclic olefin resin in Layer B is preferably 10% by mass or more, and more preferably 20% by mass or more, higher than the content of the cyclic olefin resin in Layer A.
[0037] The content of the cyclic olefin resin in Layer B is preferably 30% by mass or more, and more preferably 40% by mass or more, relative to the total mass of Layer B (100% by mass), from the viewpoints of improving adhesion to Layer C, improving water vapor barrier properties, and improving formability. From the viewpoints of improving adhesion to Layer A and improving formability, the content is preferably 70% by mass or less, and more preferably 60% by mass or less.
[0038] In addition, it is preferable that the B layer of the sealant film of the present invention contains, in addition to the cyclic olefin resin, a compatibilizer for the cyclic olefin resin and the polypropylene resin (hereinafter, sometimes referred to as a compatibilizer), which can improve the adhesion with the A layer and the C layer, and when the B layer further contains a polypropylene resin, can favorably control the dispersion state of the resin in the B layer, thereby improving the water vapor barrier property and moldability.
[0039] The content of the compatibilizer is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, relative to 100% by mass of the total mass of layer B, from the viewpoint of favorably controlling the adhesion with layer A and layer C and the dispersion state of the cyclic olefin resin and other resins in layer B. Moreover, the upper limit of the content of the compatibilizer in layer B is more preferably 20% or less, and even more preferably 10% or less, from the viewpoint of improving the water vapor barrier property.
[0040] Examples of the compatibilizer include high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-1-pentene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene-propylene-butene copolymer, styrene-ethylene-butylene-styrene copolymer, styrene-ethylene-propylene-styrene copolymer, or styrene-based copolymer resin (styrene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer), propylene-α-olefin copolymer, It is preferable to use one or more compatibilizers selected from the group consisting of ethylene and vinyl carboxylate copolymers, ethylene-vinyl acetate copolymers (EVA), ethylene-vinyl propionate copolymers, ethylene-vinyl butanoate copolymers, and copolymers of ethylene and α,β-unsaturated carboxylic acid alkyl esters, such as ethylene-methyl acrylate copolymers (EMA), ethylene-ethyl acrylate copolymers (EEA), ethylene-butyl acrylate copolymers (EBA), and ethylene-methyl methacrylate copolymers (EMMA).
[0041] The melt flow rate (MFR) of the compatibilizer measured at 230°C under a load of 21.18 N is preferably 1.0 g / 10 min or more, and more preferably 2.0 g / 10 min or more, from the viewpoints of film-forming property and dispersibility in cyclic polyolefin resins and other resins.
[0042] The B layer of the sealant film of the present invention preferably contains a thermoplastic resin other than the cyclic olefin resin and the compatibilizer. The thermoplastic resin may be the polypropylene resin suitable for the A layer described above or the thermoplastic resin suitable for the A layer, and among them, the polypropylene resin is preferred from the viewpoint of improving the adhesion with the A layer and from the viewpoint of achieving both the seal strength at high temperatures, the water vapor barrier property, and the moldability.
[0043] The content of the thermoplastic resin other than the cyclic olefin resin and the compatibilizer suitable for Layer B, when the entire Layer B is taken as 100% by mass, is preferably 30% by mass or more, and more preferably 40% by mass or more, from the viewpoint of achieving both adhesion to Layer A, seal strength at high temperatures, and moldability. Moreover, the content of the thermoplastic resin is preferably 70% by mass or less, and more preferably 60% by mass or less, from the viewpoint of achieving both adhesion to Layer A and Layer C, and water vapor barrier property.
[0044] The sealant film of the present invention is a sealant film having at least an A layer, a B layer, and a C layer in this order, and it is preferable that the B layer has a bicontinuous structure consisting of a cyclic olefin resin and other resins, and it is preferable that the A layer and the C layer contain a total of 60% by mass or more of a resin selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of the A layer and the C layer is 100% by mass, respectively. In other words, it is preferable that the A layer contains a total of 60% by mass or more of a resin selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of the A layer is 100% by mass, and the C layer contains a total of 60% by mass or more of a resin selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of the C layer is 100% by mass. As the cyclic olefin resin contained in each layer, the cyclic olefin resin suitable for the A layer described above can be preferably used. As the other resin contained in layer B, the above-mentioned compatibilizer suitable for layer B, the cyclic olefin resin suitable for layer B, and a thermoplastic resin other than the compatibilizer can be used.
[0045] The olefin resins other than the cyclic olefin resins contained in layers A and C include high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-1-pentene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene-propylene-butene copolymer, homopolypropylene, random copolymer of propylene and ethylene and / or butene-1, block copolymer containing homopolypropylene and ethylene-propylene copolymer, propylene-α-olefin copolymer, etc. It is preferable to use one or more olefin-based resins selected from copolymers of ethylene and vinyl carboxylate such as ethylene-vinyl acetate copolymer (EVA), ethylene-vinyl propionate copolymer, and ethylene-vinyl butanoate copolymer, copolymers of ethylene and α,β-unsaturated carboxylic acid alkyl ester such as ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-butyl acrylate copolymer (EBA), and ethylene-methyl methacrylate copolymer (EMMA). Among olefin-based resins other than these cyclic olefin-based resins, it is more preferable to use one or more polypropylene-based resins selected from homopolypropylene, random copolymers of propylene and ethylene and / or butene-1, and block copolymers containing homopolypropylene and ethylene-propylene copolymer for layer A.
[0046] The co-continuous structure defined in the present invention can be evaluated by observing a cross section of the sealant film in the width direction (the direction perpendicular to the machine direction when the sealant film is formed)-thickness direction with a scanning electron microscope or a transmission electron microscope. Specifically, when observed at 2,000x, 3,000x, 4,000x, 5,000x, 7,500x, 10,000x, 15,000x, and 20,000x magnifications, it can be determined that a sea-island structure is formed if circular or elliptical domains are scattered in the matrix as shown in Figure 1 at any magnification. Similarly, observation was performed at magnifications of 2,000x, 3,000x, 4,000x, 5,000x, 7,500x, 10,000x, 15,000x, and 20,000x, and a co-continuous structure was defined as a structure in which, at least at any one of the magnifications, the length of the interface between two or more resins constituting layer B was 10 times or more the maximum dispersed diameter and at least an amorphous structure was present, as shown in Figure 2. Furthermore, if a sea-island structure or co-continuous structure cannot be confirmed despite the use of two or more incompatible resins in layer B, it is preferable to confirm the dispersion state by dyeing or element mapping.
[0047] The C layer of the sealant film of the present invention preferably contains a cyclic olefin resin, and the content of the cyclic olefin resin in the C layer is preferably 60% by mass or more, more preferably 70% by mass or more, based on the total mass (100% by mass) of the C layer, from the viewpoint of improving the water vapor barrier property. The content of the cyclic olefin resin in the C layer is preferably 90% by mass or less, from the viewpoint of improving the formability and the adhesion with the B layer.
[0048] Furthermore, from the viewpoint of improving adhesion with layer B and improving formability, layer C of the present invention may contain a thermoplastic resin other than a cyclic olefin resin, and as such a thermoplastic resin, a compatibilizer that is preferably used in layer B, or a thermoplastic resin other than a cyclic olefin resin or a compatibilizer that is preferably used in layer B, may be preferably used.
[0049] The sealant film of the present invention preferably has three layers, A layer, B layer, and C layer, in this order. Having three layers, A layer, B layer, and C layer, in this order means that A layer and B layer, and B layer and C layer are directly in contact with each other without any other layer therebetween. In addition, depending on the purpose, another layer may be laminated on the A layer and / or C layer to form a laminated structure of four or more layers. For example, from the viewpoint of improving molding, it is preferable to have a four-layer structure having A layer, B layer, C layer, and B layer directly in this order, and it is more preferable to have a five-layer structure having A layer, B layer, C layer, B layer, and A layer in this order. In addition, when the sealant film of the present invention includes two or more A layers, it may include a structure including two or more layers of one type of A layer having the same composition and thickness, or may include a structure including two or more types of A layers having different compositions, thicknesses, etc. within the range satisfying the configuration requirements of the present invention. The same applies when the sealant film of the present invention contains two or more B layers or two or more C layers, and it may be configured to contain one type of B layer or C layer, or to contain two or more types of B layer or C layer.
[0050] In addition to Layer A, Layer B, and Layer C, the sealant film of the present invention may be provided with, for example, a layer for improving adhesion to a barrier layer described below, or a functional layer for further improving heat resistance, water vapor barrier properties, formability, flexibility, etc., but from the viewpoint of achieving sufficient seal strength at high temperatures, it is preferable that at least one surface of the sealant film is composed of Layer A. Furthermore, when the sealant film of the present invention is used for an exterior packaging material, it is more preferable to laminate the film so that Layer A is on the surface layer side of the exterior packaging material.
[0051] The sealant film of the present invention preferably has a static friction coefficient between at least one surface of 0.5 or less, more preferably 0.4 or less, and even more preferably 0.3 or less. As described above, the sealant film of the present invention preferably has at least one surface composed of layer A, and the static friction coefficient between the surfaces of layer A is preferably within the above-mentioned preferred range, which provides slipperiness when the sealant film of the present invention is molded into a pouch, improving moldability.
[0052] In the sealant film of the present invention, in order to improve the slipperiness and make the static friction coefficient between at least one surface 0.5 or less, it is preferable that the A layer located on at least one surface of the sealant film contains a lubricant. The lubricant is not particularly limited, but fatty acid amide, metal soap, fluorine-based polymer, silicone-based lubricant, fatty acid, vegetable oil, etc. can be used, and fatty acid amide is preferably used from the viewpoint of solubility in the thermoplastic resin layer. As the fatty acid amide, it is preferable to use one or more fatty acid amides selected from saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides.
[0053] The saturated fatty acid amide is preferably one or more saturated fatty acid amides selected from lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide, and the unsaturated fatty acid amide is preferably oleic acid amide and / or erucic acid amide.
[0054] The substituted amide is not particularly limited, but examples thereof include N-oleyl palmitic acid amide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, etc. The methylol amide is not particularly limited, but examples thereof include methylol stearic acid amide, etc.
[0055] The saturated fatty acid bisamide is not particularly limited, but examples thereof include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, and N,N'-distearyl sebacic acid amide.
[0056] The unsaturated fatty acid bisamide is not particularly limited, but examples thereof include ethylene bisoleamide, ethylene biserucamide, hexamethylene bisoleamide, and N,N'-dioleylsebacamide.
[0057] The fatty acid ester amide is not particularly limited, but examples thereof include stearamide ethyl stearate, etc. The aromatic bisamide is not particularly limited, but examples thereof include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-cystearyl isophthalic acid amide, etc.
[0058] Methods for incorporating these lubricants into layer A located on at least one surface of the sealant film include incorporating the lubricant into the material constituting layer A beforehand, or incorporating the lubricant into the material constituting layers other than layer A, such as layer B or layer C, to form a sealant film, and then subjecting the film to a heat aging treatment or the like to transfer the lubricant to layer A.
[0059] The content of the lubricant is not particularly limited, but when the mass of the entire sealant film is taken as 100 mass%, the lower limit is preferably 100 ppm by mass, and the upper limit is preferably 10,000 ppm by mass, and more preferably 3,000 ppm by mass. If the content of the lubricant is less than 100 ppm by mass, the amount of the lubricant precipitated on the surface of the sealant film may be insufficient, resulting in insufficient slipperiness, and if it is more than 10,000 ppm by mass, the lubricant may be excessively precipitated on the surface, resulting in white powder.
[0060] The sealant film of the present invention has at least one surface having a ten-point average roughness of preferably 2.0 μm or more, more preferably 3.0 μm or more. As described above, the sealant film of the present invention has at least one surface being composed of layer A, and the ten-point average roughness of the layer A surface is preferably within the above-mentioned preferred range, and more preferably the ten-point average roughness of the layer A surface having a static friction coefficient of 0.5 or less is within the above-mentioned preferred range. This provides slipperiness when the sealant film of the present invention is molded into a pouch, improving moldability.
[0061] The sealant film of the present invention has a ten-point average roughness of at least one surface of 2.0 μm or more, and preferably contains particles in the A layer located on at least one surface in order to enhance slipperiness. Examples of the particles include inorganic particles and resin particles, and the inorganic particles are preferably one or more inorganic particles selected from inorganic oxide particles (silica particles, alumina particles, titanium oxide particles, etc.), inorganic carbonate particles (calcium carbonate particles, barium carbonate particles, etc.), and inorganic silicate particles (aluminum silicate particles, talc particles, kaolin particles, etc.). The resin particles are preferably one or more resin particles selected from acrylic resin particles, polyolefin resin particles (polyethylene resin particles, polypropylene resin particles), and polystyrene resin particles.
[0062] The particles may be of one type or of two or more types. When two or more types are used, it is preferable to use two or more types of particles with different average particle diameters, and in this case, it is possible to obtain an effect that it is easy to make the distribution of surface roughness uniform. In addition, it is preferable to use particles with a specific gravity of 3 or less, and in this case, it is possible to obtain an effect that the incompatible particles can be easily dispersed uniformly in the layer.
[0063] Each layer of the sealant film of the present invention may contain additives other than those described above. For example, there may be mentioned a compatibilizer other than those described above for increasing the dispersibility and interfacial strength of the resin constituting each layer, an additive for improving the interlayer adhesion of each layer, an antioxidant, a plasticizer, an ultraviolet absorber, an antifungal agent, a colorant (pigment, dye, etc.), an antistatic agent, an antirust agent, a moisture absorber, an oxygen absorber, etc.
[0064] The water vapor transmission rate of the sealant film of the present invention at 60°C and 90% RH is 3g mm / m 2 / day or less is preferable, and 2g·mm / m 2 / day or less is preferable, and 1.5g·mm / m 2 / day or less is more preferable. 2 By setting the aging time to 100 s / day or less, even when the sealant film of the present invention is used as an exterior material film for a secondary battery, moisture intrusion can be suppressed, and an increase in the internal pressure, expansion, and explosion of the exterior material can be suppressed, and deterioration of the battery can be suppressed.
[0065] As a method for controlling the water vapor permeability of the sealant film within the above-mentioned preferred range and improving the water vapor barrier properties of the sealant film, the above-mentioned methods can be used, and examples thereof include a method in which the cyclic olefin resin in layer C is 60 mass% or more relative to 100 mass% of the total mass of layer C, a method in which the cyclic olefin resin in layer B is 30 mass% or more relative to 100 mass% of the total mass of layer B, and a method in which the components other than the cyclic olefin resin in layer B and layer C are polypropylene resin.
[0066] In order to prevent the heat-sealed portion from being opened when used at high temperatures, the sealant film of the present invention preferably has a peel strength of 10N / 15mm or more, more preferably 15N / 15mm or more, in an atmosphere of 100°C after the A layers are heat-sealed together. As a method for making the peel strength 10N / 15mm or more, the above-mentioned method for improving the high-temperature sealability can be preferably used. The peel strength is evaluated by the method described in the Examples below.
[0067] The thickness of the sealant film of the present invention is not particularly limited, but the lower limit is preferably 10 μm, more preferably 30 μm, and the upper limit is preferably 500 μm, more preferably 300 μm or less, even more preferably 200 μm or less, and most preferably 120 μm or less. If the thickness of the sealant film is thinner than 10 μm, sufficient seal strength may not be obtained when the exterior material using the sealant film of the present invention is heat sealed. If the thickness of the sealant film is thicker than 500 μm, the rigidity may be too high and it may not be possible to roll it up.
[0068] The sealant film of the present invention has excellent sealing strength at high temperatures, water vapor barrier properties, and moldability, and therefore can be preferably used as an exterior material for secondary batteries, and can be more preferably used as an exterior material for all-solid-state batteries that are used in higher temperature environments than conventional batteries. As members constituting the exterior material other than the sealant film, known members can be used, such as a heat-resistant substrate layer, a barrier layer, and an adhesive layer.
[0069] By having a heat-resistant substrate layer, it is possible to sufficiently secure insulation and improve the physical strength and impact resistance of the exterior material. A known material can be used for forming the heat-resistant substrate layer, and examples thereof include polyamide films such as nylon films, polyester films, and the like, and these stretched films are preferably used. Among them, it is particularly preferable to use biaxially stretched polyamide films such as biaxially stretched nylon films, biaxially stretched polybutylene terephthalate (PBT) films, biaxially stretched polyethylene terephthalate (PET) films, or biaxially stretched polyethylene naphthalate (PEN) films. The nylon film is not particularly limited, and examples thereof include 6 nylon film, 6,6 nylon film, and MXD nylon film. The heat-resistant substrate layer may be formed of a single layer, or may be formed of a multilayer structure consisting of, for example, a polyester film / polyamide film (such as a multilayer structure consisting of a PET film / nylon film).
[0070] The thickness of the heat-resistant base layer is preferably 2 μm to 200 μm. The upper limit of the thickness of the heat-resistant base layer is more preferably 100 μm or less, and even more preferably 50 μm or less. The lower limit of the thickness of the heat-resistant base layer is more preferably 5 μm or more. By setting the thickness to the above-mentioned preferable lower limit or more, it becomes easy to ensure sufficient strength as an exterior material, and by setting the thickness to the above-mentioned preferable upper limit or less, it becomes easy to reduce stress during molding such as stretch molding and drawing molding, thereby improving moldability.
[0071] The barrier layer plays a role of imparting a barrier property that prevents the intrusion of oxygen and moisture to the exterior material. As the barrier layer, a known one can be used, and is not particularly limited. For example, aluminum foil, SUS foil (stainless steel foil), copper foil, etc. can be mentioned, and among them, aluminum foil and SUS foil (stainless steel foil) are preferably used. The thickness of the barrier layer is preferably 5 μm to 120 μm. By being 5 μm or more, it is easy to prevent the occurrence of pinholes during rolling when manufacturing the barrier layer, and by being 120 μm or less, it is easy to reduce stress during molding such as stretch molding and drawing molding, and to improve moldability. Among them, the thickness of the barrier layer is more preferably 10 μm to 80 μm.
[0072] The packaging material of the present invention may have an adhesive layer between the base layer and the barrier layer, for example, for the purpose of increasing the adhesion between these layers, if necessary. Similarly, an adhesive layer may be provided between the barrier layer and the sealant film, if necessary. Furthermore, other functional layers may be provided within a range that does not impair the effects of the present invention. Known adhesive layers can be used for the adhesive layer.
[0073] The structure of the exterior material using the sealant film of the present invention can be, for example, heat-resistant substrate layer / adhesive layer / barrier layer / adhesive layer / sealant film, in which case the sealant film of the present invention and the heat-resistant substrate layer / adhesive layer / barrier layer can be laminated via an adhesive layer (dry lamination method). As another method, the resin constituting the sealant film can be melt-extruded onto a laminate consisting of a heat-resistant substrate layer / adhesive layer / barrier layer, and then directly laminated onto the laminate (thermal lamination method).
[0074] The total thickness of the packaging material using the sealant film of the present invention is not particularly limited, but from the viewpoints of cost reduction, energy density improvement, etc., it is preferably 1000 μm or less, more preferably 800 μm or less, and even more preferably 500 μm or less, and from the viewpoint of maintaining the function of the packaging material to protect the battery element, it is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more.
[0075] When the sealant film of the present invention is used for an exterior material, it is preferable to laminate the A layer of the sealant film on the surface side of the exterior material. However, if the molding temperature when molding the exterior material into a pouch is too high, the resin used in the A layer may be fused to the molding machine, resulting in reduced productivity. In addition, if a lubricant or the like is added to the A layer to improve moldability, if the molding temperature is too high, the lubricant may be excessively precipitated on the surface of the A layer, contaminating the molding machine and reducing productivity. In addition, if the molding temperature is too high, additives other than the lubricant and low molecular weight components such as oligomers may be excessively precipitated on the surface of the A layer from the A layer or other layers of the sealant film. If the above-mentioned lubricant, other additives, and low molecular weight components are excessively precipitated, sufficient heat seal strength may not be obtained when heat sealing the A layers of the exterior material of the present invention. In such a case, when the exterior material of the present invention is used for a sulfide-based all-solid-state battery, water vapor is likely to penetrate from the seal portion at the end face of the pouch, and hydrogen sulfide, a harmful substance, may be generated, causing an increase in the internal pressure of the pouch, corroding the electrodes and the barrier layer described below, etc., which may result in deterioration of the battery. For this reason, the molding temperature when molding the exterior material into a pouch shape is preferably 100°C or lower, and more preferably 50°C or lower.
[0076] Methods for controlling the molding temperature include methods for preferably controlling the type and content of materials constituting each layer of the sealant film of the present invention, the glass transition temperature of the cyclic olefin resin used in the sealant film of the present invention, the static friction coefficient between one surface of the sealant film of the present invention, and the ten-point average roughness of one surface of the sealant film of the present invention.
[0077] The packaging material using the sealant film of the present invention is preferably used as a packaging material for secondary batteries such as lithium ion batteries and all-solid-state lithium secondary batteries using a non-aqueous electrolyte, and is particularly preferably used as a packaging material for all-solid-state batteries because of its excellent seal strength at high temperatures, water vapor barrier properties, and moldability. In addition, because the sealant film of the present invention has excellent moldability, the packaging material using the sealant film of the present invention is particularly preferably used for molding a molded product with a drawing depth of 5 mm or more.
[0078] Furthermore, a secondary battery using the sealant film of the present invention can be preferably used as a secondary battery for electric devices such as electric automobiles and electric aircraft. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0080] (1) Melt flow rate (MFR) The MFR of the raw materials used in the examples and comparative examples was measured using a melt indexer manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with JIS K7210-1997 under a load of 21.18 N. The measurement temperature was 190°C for PE and 230°C for PP and CEBC.
[0081] (2) Melt Viscosity Using a Toyo Seiki Capillograph (1D), the temperature was 230°C and the shear rate was 121 s -1 The melt viscosity of the cyclic olefin resin was measured.
[0082] (3) Melting point 5 mg of PP, PE, and CEBC used in the A layer of the examples or comparative examples were collected in an aluminum pan, and using a differential scanning calorimeter (Seiko Instruments EXSTAR DSC6220), the temperature was raised from room temperature to 250°C under a nitrogen atmosphere, then held at 250°C for 5 minutes, then lowered from 250°C to 25°C, held at 25°C for 5 minutes, and then heated again to 250°C. The endothermic peak temperature was taken as the melting point of each resin, and the highest melting point among the melting points of the raw materials used in the A layer was taken as the melting point of the A layer. In addition, when there were two or more endothermic peaks, the peak on the higher temperature side was taken as the melting point of the raw material. In addition, the temperature rise rate and temperature fall rate were measured at 20°C / min.
[0083] (4) Glass transition temperature In accordance with ISO11357-1 (2016) and ISO11357-2 (2020), 5 mg of COC1 and COC2 used in the examples or comparative examples were placed in an aluminum pan and heated from room temperature to 250°C at a rate of 10°C / min under a nitrogen atmosphere using a differential scanning calorimeter (Seiko Instruments EXSTAR DSC6220), to evaluate the glass transition point of the cyclic olefin resin.
[0084] (5) Thickness of each layer The thickness of each layer of the sealant film was measured by preparing a cross-section of the sealant film in the width direction (perpendicular to the machine direction when the sealant film was formed)-thickness direction with a width of 5 mm using a microtome method, and the cross-section was platinum-coated to obtain an observation sample. Next, the cross-section of the sealant film was observed at an arbitrary magnification using a Hitachi field emission scanning electron microscope (S-4800), and the thickness of each layer was measured at 10 arbitrary points on the observation image, and the average value was determined as the thickness of each layer.
[0085] (6) Dispersion state of layer B Using the observation sample prepared in (5), the area including the B layer of the sealant film was observed at 2,000x, 3,000x, 4,000x, 5,000x, 7,500x, 10,000x, 15,000x, and 20,000x magnifications with a Hitachi field emission scanning electron microscope (S-4800), and the dispersion state was evaluated according to the following criteria. When the sealant film had two B layers, both B layers were observed and evaluated, but in the examples and comparative examples evaluated this time, the two B layers showed the same dispersion state. Cocontinuous: At least one amorphous structure was observed in which the interface length was 10 times or more the dispersion diameter. Sea-island: At all magnifications, only circular or elliptical domains were scattered throughout the matrix. Uniform: Only one type of resin was used in layer B, and no dispersed structure was observed.
[0086] (7) Coefficient of static friction Using an apparatus conforming to JIS K7125-1985, the static friction coefficient between the surfaces of layer A that had not been in contact with the cooling roll during cast molding was measured with a load of 100 g on the sample surface and a moving speed of 20 cm / min.
[0087] (8) Ten-point average roughness The ten-point average roughness Rz was measured using a high-precision micro-profile measuring instrument (SURFCORDER ET4000A) manufactured by Kosaka Laboratory in accordance with JIS B0601-1994, on the surface of layer A that was not in contact with the cooling roll during cast molding, under the following measurement conditions. Note that for one type of sealant film, measurements were taken three times in each direction, and the arithmetic average value of a total of six measurements was used. Measurement range: Machine direction (MD) 0.2mm, Transverse direction (TD) 2mm Measurement pitch: Machine direction (MD) 10 μm, Width direction (TD) 0.2 μm Stylus: Diamond stylus with a tip radius of 2.0 μm Load: 100μN Cutoff: 0.8mm.
[0088] (9) Water vapor permeability Using the sealant films prepared in the examples and comparative examples, measurements were performed at 60°C, 90% relative humidity, and 24 hours in accordance with JIS Z0208-1976 (cup method), and the water vapor transmission rate was calculated by converting it to a value per mm thickness. The sealant film was set so that the layer A that was not in contact with the cooling roll during cast molding was on the cup side.
[0089] (10) Creating exterior materials A commercially available nylon (thickness 25 μm, one side corona treated) was dry laminated to one side of a commercially available aluminum foil (40 μm) via a commercially available adhesive (manufactured by DIC, product name "LX500 / KO55") so that the adhesive was applied to the corona treated side of the nylon, and then the aluminum foil was dry laminated to the other side of the aluminum foil where the nylon was not laminated via a commercially available adhesive (epoxy adhesive) so that the A layer that was not in contact with the cooling roll during cast molding of the sealant film became the surface of the exterior material. The sealant film was previously corona treated on the adhesive side with the aluminum foil, and dry laminated so that the adhesive was applied to the corona treated side. After that, it was heated in an oven at 40 ° C for 5 days and used as an exterior material.
[0090] (11) Peel strength (seal strength) in a 100°C atmosphere after heat sealing the A layers together Two pieces of 100mm x 15mm exterior materials were heat-sealed with the surface of layer A facing inward using a 15mm-wide flat heat sealer under the conditions of a temperature of 200°C for the upper and lower seal bars, a sealing pressure of 0.3MPa, and a sealing time of 4 seconds to create a sample (size of heat-sealed portion in sample: width 15mm, length 15mm). Two types of samples were created, one with the longitudinal direction being the machine direction (MD) of the exterior material, and the other with the longitudinal direction being the width direction (TD) of the exterior material. Then, using a tensile tester (Orientec's universal testing machine "Tensilon" (registered trademark)), the samples were peeled five times each in the machine direction (MD) and width direction (TD) of the exterior material in an atmosphere of 100°C, at a peel angle of 180° and a speed of 300mm / min. The arithmetic average of the peel load in the range of 5mm to 10mm from the starting point of peeling was taken as the seal strength of each sample, and the arithmetic average of the seal strengths measured five times in each of the machine direction (MD) and cross direction (TD) (average of a total of 10 times) was taken as the seal strength of the exterior material, and a value of 10N / 15mm or more was determined to have good sealability at high temperatures.
[0091] (12) Formability Using a deep drawing molding device manufactured by JMT Corporation, the exterior material was cut to 100 mm x 150 mm and deep drawn into a rectangular shape with a depth of 8 mm under the following molding conditions so that the surface of the thermoplastic resin layer A of the exterior material was located inside the accommodating recess of the molded body, and the product was evaluated according to the following criteria A to C.
[0092] <Molding conditions> Male mold: 89mm x 54mm, R=2mm Female mold: 118mm x 175mm, R=2mm Wrinkle suppression pressure: 0.5MPa (air source pressure) Material: Stainless steel. Molding temperature: Molding was performed by increasing the temperature from 50°C to 100°C in increments of 10°C. The inner surface of the storage recess of the obtained molded body was visually observed, and the lowest moldable temperature without any damage such as cracks was determined as the molding temperature for the exterior material.
[0093] <Evaluation criteria> A: Molding temperature is 50℃ B: Molding temperature is 60℃~100℃ C: The exterior material was damaged at 100°C.
[0094] The raw materials constituting the sealant films of the examples and comparative examples are shown below. COC1: Mitsui Chemicals COC (APEL(trademark) APL6509T), glass transition temperature: 80°C, melt viscosity: 600 Pa s COC2: Mitsui Chemicals COC (APEL(trademark) APL6011T), glass transition temperature: 105°C, melt viscosity: 740 Pa s PP; a commercially available ethylene propylene random copolymer with melting point of 138°C and MFR of 3g / 10min (measured at 230°C). CEBC: Crystalline olefin-ethylene-butylene-crystal olefin block copolymer (Dynaron® 6200P) manufactured by JSR, melting point 97°C, MFR 2.5g / 10min (measured at 230°C) PE; Commercially available linear low-density polyethylene with melting point of 113°C and MFR of 3.8g / 10min (measured at 190°C). PE particles MB: A masterbatch consisting of 10% by mass of polyethylene particles having an average particle size of 10 μm (Mippelon (registered trademark) PM-200 manufactured by Mitsui Chemicals) and 90% by mass of the above-mentioned PP. EBSA; commercially available ethylene bis stearic acid amide Example 1 The raw materials for layers A, B, and C shown in Table 1 were melt-kneaded in advance in a twin-screw extruder at 250°C and used as the raw materials for layers A, B, and C. A five-layer coextrusion was performed using a T-die at 250°C in the order of A layer, B layer, C layer, B layer, and A layer so that the thicknesses of A layer were 10 μm, B layer 5 μm, C layer 50 μm, B layer 5 μm, and A layer 10 μm, and the five-layer sealant film was cast on a cooling roll at 40°C to obtain a five-layer sealant film with a thickness of 80 μm, and various evaluations were performed.
[0095] (Examples 2 to 5, Comparative Example 1) The same procedure was followed as in Example 1, except that the raw materials for layers A, B, and C were as shown in Table 1.
[0096] Comparative Example 2 The same procedure as in Example 1 was followed, except that the raw materials for layers A, B, and C were as shown in Table 1, and the five layers were co-extruded in this order so that layer A was 5 μm, layer B was 5 μm, layer C was 60 μm, layer B was 5 μm, and layer A was 5 μm.
[0097] Comparative Example 3 The same procedure as in Example 1 was followed, except that the raw materials for layers A and C were as shown in Table 1, and the three layers were co-extruded at 250°C using a T-die in this order so that layer A was 20 μm, layer C was 40 μm, and layer A was 20 μm, to obtain a three-layer sealant film with a thickness of 80 μm.
[0098] The sealant films of Examples 1 to 5 and the packaging materials using these films were excellent in sealing property, water vapor barrier property, and moldability at high temperatures, and among them, Examples 1 and 2 were particularly excellent in the balance of sealing property, water vapor barrier property, and moldability at high temperatures. On the other hand, Comparative Examples 1 to 3 were inferior in sealing property, water vapor barrier property, and moldability at high temperatures.
[0099] [Table 1] [Industrial Applicability]
[0100] The sealant film for exterior packaging of the present invention has excellent sealing properties, water vapor barrier properties, and formability at high temperatures, and can therefore be preferably used as a sealant film for exterior packaging of secondary batteries, in particular as a sealant film for exterior packaging of all-solid-state batteries.
Claims
1. A sealant film having at least an A layer, a B layer, and a C layer directly in this order, wherein the A layer has a melting point of 135°C or higher and contains a polypropylene-based resin, and at least the B layer and the C layer contain a cyclic olefin-based resin, and the content of the cyclic olefin-based resin in each layer is greatest in the C layer, the B layer, and the A layer in that order.
2. A sealant film having at least a layer A, a layer B, and a layer C directly in this order, wherein the layer B has a co-continuous structure consisting of a cyclic olefin resin and other resins, the layer A contains a total of 60 mass% or more of resins selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of the layer A is taken as 100 mass%, and the layer C contains a total of 60 mass% or more of resins selected from a cyclic olefin resin and an olefin resin other than a cyclic olefin resin when the total mass of the layer C is taken as 100 mass%.
3. The sealant film according to claim 1 or 2, wherein the layer B contains a cyclic olefin resin in an amount of 30% by mass or more and 70% by mass or less relative to 100% by mass of the total mass of the layer B.
4. The sealant film according to claim 3 , wherein the layer B contains a compatibilizer for the cyclic olefin resin and the polypropylene resin.
5. The sealant film according to claim 1 or 2, wherein the C layer contains 60 mass% or more of a cyclic olefin resin relative to 100 mass% of the total mass of the C layer.
6. 3. The sealant film according to claim 1, which comprises five layers laminated directly in the following order: layer A, layer B, layer C, layer B and layer A.
7. 3. The sealant film according to claim 1, wherein at least one of the surfaces has a static friction coefficient of 0.5 or less and a ten-point average roughness of 2.0 μm or more.
8. Water vapor transmission rate at 60℃ and 90% RH is 3g・mm / m 2The sealant film according to claim 1 or 2, wherein the sealant film has a viscosity of 1000:1 or less.
9. 3. The sealant film according to claim 1, wherein the peel strength in an atmosphere at 100°C after the A layers are heat-sealed to each other is 10 N / 15 mm or more.
10. The sealant film according to claim 1 or 2, which is used for a molded article having a drawing depth of 5 mm or more.
11. The sealant film for exterior materials according to claim 1 or 2, which is used as an exterior material for an all-solid-state battery.
12. An exterior material for a secondary battery, comprising the sealant film according to claim 1 or 2.
13. A secondary battery comprising the exterior packaging material according to claim 12.
14. An electrically-powered device comprising the secondary battery according to claim 13.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2007026682A
Battery and external package member for battery
JP2008293909A
Packaging material for electrochemical cell
JP2015038881A
Packaging material and packaging body for all-solid lithium ion battery
JP2021057231A
Outer package material for electric power storage device and electric power storage device using the same
JP2021108263A
